2012
DOI: 10.1007/s00540-012-1540-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the use of the Valsalva maneuver and the eutectic mixture of local anesthetics (EMLA®) to relieve venipuncture pain: a randomized controlled trial

Abstract: The Valsalva maneuver yields similar results to the EMLA(®) in terms of pain reduction during venipuncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 26 publications
2
30
0
3
Order By: Relevance
“…Another factor that could theoretically contribute to placebo (and potentially active drug) response may be related to neurochemical effects of CO 2 delivery and/or removal of NO at the trigeminal nerve endings within the nasal cavity. Since AVP‐825 redirects exhaled air deep into the nasal cavity, it has an added advantage of broadly exposing deep intranasal structures innervated by the first branch of the trigeminal nerve to positive pressure and high airflow of exhaled air . The increased Bi‐Directional airflow (in one nostril, out the other) may locally replace the elevated levels of NO found in this region with exhaled air containing 5‐6% CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that could theoretically contribute to placebo (and potentially active drug) response may be related to neurochemical effects of CO 2 delivery and/or removal of NO at the trigeminal nerve endings within the nasal cavity. Since AVP‐825 redirects exhaled air deep into the nasal cavity, it has an added advantage of broadly exposing deep intranasal structures innervated by the first branch of the trigeminal nerve to positive pressure and high airflow of exhaled air . The increased Bi‐Directional airflow (in one nostril, out the other) may locally replace the elevated levels of NO found in this region with exhaled air containing 5‐6% CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The decreased hypersensitivity was reversed by IV atropine, suggesting involvement of muscarinic cholinergic receptors . Suren et al found that the Valsalva maneuver was comparable to local anesthetic gel in reducing venipuncture pain …”
Section: Recent Trials and Research On Vnsmentioning
confidence: 99%
“…In the present Breath Powered device, it is postulated that the oscillating capsule and airflow may significantly enhance exchange of air in upper narrow parts of the nose, as in part observed in response to humming and pulsating nebulizers . In addition, there are reasons to hypothesize that potential positive effects mediated by the positive air pressure, rapid vibrations produced by the rattling capsule, and the removal of NO may all play a role in alleviating migraine headache . One or more of these, or other, device‐related mechanisms may contribute to the high response rate in the placebo groups in the trials with Breath Powered powder delivery in migraine patients.…”
Section: Optinose Breath Powered Deliverymentioning
confidence: 99%